ASSOCIATION BETWEEN RHEUMATOID ARTHRITIS AND HEALTH-RELATED QUALITY OF LIFE IN KOREAN WOMEN AGED 50 YEARS AND OVER - Park, Hyejin (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The purpose of this study is to evaluate the association between rheumatoid arthritis (RA) and health-related quality of life (HRQoL) in Korean women. Methods: Participants (n=2068) aged 50 years or older were selected from Korea National Health and Nutrition Examination Survey (KNHANES) 2005-2008. Sociodemographic characteristics, medical history of RA, and EuroQol-5 dimension were obtained from the KNHANES dataset. Results: The results revealed that demographic variables, including age, education level, income, exercise, smoking, and alcohol drinking, were important factors associated with HRQoL. In this study, RA was an important factor affecting HRQoL in Korean women. The adjusted odds ratio for HRQoL in participants with RA was 2.15 (95% confidence interval [CI]: 1.46-3.18, p=0.001) in mobility, 2.30 (95% CI: 1.60-3.32, p<0.001) in usual activities, and 3.41 (95% CI: 2.20-5.28, p<0.001) in pain/discomfort. Conclusion: These findings suggest that there is a strong associationbetween RA and HRQoL and preventing and controlling RA may significantly improve the quality of life for elderly Korean women. Â 